2016
DOI: 10.1136/heartjnl-2015-308453
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise test and sudden cardiac death risk in hypertrophic cardiomyopathy

Abstract: Our data suggest that the VE/VCO2 slope might improve SCD risk stratification, particularly in those HCM categories classified at low-intermediate SCD risk according to contemporary guidelines. There is a need for further larger studies, possibly on independent cohorts, to confirm our preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 36 publications
3
46
0
1
Order By: Relevance
“…Uniform predictor definitions were used, except in one study23 where family history of SCD was defined as HCM-related SCD in at least one first degree or other relatives ≤50 years and unexplained syncope had to be recent (≤5 years of baseline evaluation). The same study used ATP as a surrogate of SCD23 but all other studies used the same SCD endpoint definition as stated in the Methods section 3 21 24. Following communication with the study authors, ATP endpoints (and 32 patients reported in both HCM Risk-SCD and Magrì et al 23) were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniform predictor definitions were used, except in one study23 where family history of SCD was defined as HCM-related SCD in at least one first degree or other relatives ≤50 years and unexplained syncope had to be recent (≤5 years of baseline evaluation). The same study used ATP as a surrogate of SCD23 but all other studies used the same SCD endpoint definition as stated in the Methods section 3 21 24. Following communication with the study authors, ATP endpoints (and 32 patients reported in both HCM Risk-SCD and Magrì et al 23) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The same study used ATP as a surrogate of SCD23 but all other studies used the same SCD endpoint definition as stated in the Methods section 3 21 24. Following communication with the study authors, ATP endpoints (and 32 patients reported in both HCM Risk-SCD and Magrì et al 23) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a relationship has been reported between sudden dead risk in hypertrophic cardiomyopathy and ventilatory efficiency (Magrì et al, 2016). However, the importance of the ventilatory efficiency for sport performance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Magrì et al reported a VE/VCO 2 prognostic cut-off value of 31 for patients with hypertrophic cardiomyopathy. 27 Recently, age-dependent VE/VCO 2 slope prognostic cut-off values for HF patients have been suggested, with a different value for preserved and reduced LVEF HF patients. 28 It is of note that VE/VCO 2 slope is included in a few scores as a continuum, avoiding any cut-off value.…”
Section: Discussionmentioning
confidence: 99%